PENGARUH UKURAN, PERTUMBUHAN, DAN PROFITABILITAS PERUSAHAAN TERHADAP KOEFISIEN RESPON LABA PADA EMITEN MANUFAKTUR DI BURSA EFEK JAKARTA - Muhammad Arfan; Ira Antasari (Jurnal Telaah dan Riset Akuntansi, 2008)
The Objective of this research is to examine and analyze the influence of size, growth, and profitability, both simultaneously and partially, toward earnings response coefficient on listed companies from the manufacturing sector at the Jakarta Stock Exchange. The research type used is verificative research by sample method.     The result of this research shows that simultaneously size, growth, and profitability has significant influence toward earnings response coefficient on listed companies from the manufacturing sector at the Jakarta Stock Exchange, but partially only growth has significant influence toward earnings response coefficient. Keywords: Size, growth, profitability, and earnings response coefficient.